The Role of Supervisory and Training Practices in The Field Education Programmes in Achieving the Course Objectivesfrom the Perspective of the Student Teachers in the Faculty of Science and Arts in Sharourah (Journal of the College of Education for Women, 2020)
The present study aimed at identifying the role of supervisory and training practices in the field education program in achieving course objectives from the perspective of the student teachers in the Faculty of Science and Arts in sharourah, and its relationship to some variables (gender, specialization,estimation). To achieve this, the researcher used the descriptive-analytical method, and the study tool was designed, which consists of (24) items distributed on two axes: the objectives of field education and supervisory and training practices.Then, the study tool was applied to the research sample represented in the entire study community, which consists of (65) male and female students in the Faculty of Sciences and Arts in Sharurah Governorate in the academic year 1437-1438 AH. The results of the study indicated that the objectives of the Field Education have been achieved to a large extent , In addition, the field education program and the supervisory and training practices it included have helped in achieving these objectives, with a difference in the role from one practice to another,It was also found that there were no significant differences due to the difference in gender and estimation variables, while there were statistically significant differences due to the difference in the specialty variable in favor of the major of Islamic studies.The study recommended expanding the fields of practice in field education by updating the traditional methods.